Evaluation of anti-hypertensive activity of Ulmus wallichiana extract and fraction in SHR, DOCA-salt- and L-NAME-induced hypertensive rats. (4th December 2016) - Syed, Anees A.; Lahiri, Shibani; Mohan, Divya; Valicherla, Guru R.; Gupta, Anand P.; Riyazuddin, Mohammed; Kumar, Sudhir; Maurya, Rakesh; Hanif, Kashif; Gayen, Jiaur R.
Abstract: Ethnopharmacological relevance: Ulmus wallichiana Planchon (Himalayan Elm), a traditional medicinal plant, used in fracture healing in folk tradition of Uttarakhand, Himalaya, India. It is also used as diuretic. U. rhynchophylla, native to China, known as Gou Teng in Chinese medicine, is used for hypertension (WHO). U. macrocarpa has antihypertensive and vasorelaxant activity. However, no detailed studies related to hypertension have been reported previously, so we have explored the antihypertensive activity of U. wallichiana. Aim of the study: To investigate the pharmacological effect of ethanolic extract (EE) and butanolic fraction (BF) of U. wallichiana in hypertensive rats. Materials and methods: SHR, DOCA-salt- and L-NAME-induced hypertension models were used. Treatment was performed by oral administration of EE and BF of U. wallichiana (500 mg/kg/day and 50 mg/kg/day) for 14 days. Then blood pressure was measured by non-invasive blood pressure (NIBP) measurement technique. Invasive blood pressure (IBP) was also reported to support the NIBP data. Concentrations of plasma renin, angiotensin II (Ang II), nitrate/nitrite (NO), cGMP were estimated. Angiotensin-converting enzyme (ACE) activity and ROS activity were also estimated. Results: Blood pressure was significantly higher in SHR as compared to normotensive wistar group (170.59±0.83 mmHg vs 121.54±1.24 mmHg, respectively). SBP was increased in DOCA-salt induced group compared to their control (132.77±3.90 mmHg vs 107.85±5.95 mmHg, respectively) and L-NAME-induced group compared to their control (168.55±5.07 mmHg vs 113.03±4.13 mmHg, respectively). The treatment of extract and fraction of U. wallichiana significantly decreased the blood pressure in SHR+EE (151.26±1.85 mmHg, p<0.001), SHR+BF (140.44±1.16 mmHg, p<0.001); DOCA+EE (113.43±5.44 mmHg, p<0.05), DOCA+BF (105.09±5.12 mmHg, p<0.05) and L-NAME+EE (119.76±4.39 mmHg, p<0.001), L-NAME+BF (117.50±7.27 mmHg, p<0.001) compared to their respective diseased control groups. The plasma renin, Ang II and ACE activity were also significantly decreased and augmented the NO and cGMP levels. It also down regulated the expression of Renin, ACE, NOS3 and TGF-β1 at mRNA levels. Conclusions: The EE and BF probably reducing the BP via Renin-angiotensin-aldosterone system and NO/cGMP signaling pathway. The decrease in blood pressure may be due to presence of quercetin analogue flavonoids (2S, 3S)-(+)−3′, 4′, 5, 7-tetrahydroxydihydroflavonol-6-C-β-D-glucopyranoside; 6-Glucopyranosyl-3, 3′, 4′, 5, 7-pentahydroxyflavone; 6-Glucopyranosyl-4′, 5, 7-trihydroxyflavanone and (2 S, 3 S)-(+)−4′, 5, 7-trihydroxydihydroflavonol-6-C-β-D-glucopyranoside, may be due to its antioxidant activity. Thus EE and BF of U. wallichiana found to have the potential ability to be used as herbal medicament to treat hypertension. Graphical abstract: